PERILAKU POSESIF DALAM GAYA BERPACARAN DI KALANGAN REMAJA KOTA DENPASAR - Fadhilah, Erysa Ayu; Suka Arjawa, I Gusti Putu Bagus; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 1 No 2 (2019), 2019)
ABSTRACT   This study aims to determine directly about possessive behavior that occurs within teenagers dating relationships at the city of Denpasar. The theory used in this research is Erich Fromm's The Art of Loving (Concept of Owning and Being). As for the results of this study, among others, there are fundamental factors that become the background of the emergence of possessive attitudes carried out by each partner, including the fear of loss, the previous failure in a relationship, and so forth. Also, from several cases of possessive actions, many of the couples committed physical or verbal violence to show dominance in the relationship. The possessive relationship also has several negative and positive impacts.   Keywords: Possessive Behavior, Dating Style, Teenagers